Biomechanical Comparison of Standard Excisional Hip Arthroplasty and Modified Deep Gluteal Muscle Transfer Excisional Arthroplasty - Dueland, R. T.; Dogan, S.; Vanderby, R. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
A comparison of hind limb weight-bearing for standard hip excision (EX) vs. modified deep gluteal excision (MDG) was performed in sixteen hips of eight dogs. Using force plated technology, maximum vertical force was determined in each hind limb at a walk before and at two and four months after the operation. Recovery with both techniques was 67% at two months and 84% at four months after the operation. In conclusion, transfer of a portion of the deep gluteal muscle to the femoral osteotomy site appears not to halve any advantage over standard hip excision. The original deep gluteal transfer technique was not compared.A portion of this report was presented at the 1995 Veterinary Orthopedic Society meeting, Whistler, B.C. Canada
Keywords: Gait analysis; ground reaction force; hip arthroplasty; hip excision